How I investigate acquired megaloblastic anemia. (3rd January 2022) - Torrez, Mary; Chabot‐Richards, Devon; Babu, Daniel; Lockhart, Evelyn; Foucar, Kathryn
Abstract: In this review of megaloblastic anemia (MA), an overview of vitamin B12 and folate body requirements, biochemical pathways, and laboratory testing strategies will be provided. However, the focus of this review is the classic and unique features of MA in blood and bone marrow. Acquired MA is a benign disorder for many, but can be detrimental for some. The clinical presentation can vary considerably, and the spectrum of symptoms and signs is diverse and quite broad. Prompt recognition and therapy are critical to prevent potential irreversible damage and clinical sequelae, especially in patients with vitamin B12 deficiency. A delay in diagnosis of vitamin B12 deficiency can result in significant neurologic sequelae that may not fully resolve with treatment, including in neonates and young infants. The blood and bone marrow features in MA can closely mimic thrombocytopenic purpura, myelodysplasia, and other myeloid neoplasms. Both pancytopenia and normal MCV at presentation are common in MA and raise unique challenges for the diagnostician. Partially treated MA is also a significant diagnostic "trap". MA is highly responsive to treatment, and patients tend to improve rapidly upon treatment initiation. However, the broad range of clinical and hematologic features makes the rapid, successful diagnosis of MA a unique challenge for the hematopathologist. Even in the era of state‐of‐the‐art laboratory testing, a high suspicion is required.